JUAL BELI PAKAN TERNAK BABI DALAM HUKUM ISLAM - Rahmawati Rahmawati (MUAMALAH, 2015)
This journal titled Purchase Feed Pigs in Islamic Law The principal issues discussed  were How the concept of buying and selling in Islam and Islamic law review on buying and selling pig feed? To parse the subject matter, the author of Shariah approach and methodological approaches. The goal is to reveal in detail the concept of buying and selling according to Islamic law. Data were collected through library research which emphasizes the study of texts on theoretical and philosophic processed. Data were analyzed by using content analysis to formulate conclusions. The results showed that the sale and purchase in Islam is said to be valid if eligible, and its pillars. Among its terms and pillars. Pillars of Purchase: 1. Seller and buyer, Requirement: Baligh or mature, intelligent, not redundant state (spender), by his own will (not forced). 2. Objects or traded goods (Ma'kud Alaih). The conditions on objects that are traded are: useful, Holy, may be submitted, the property itself. 3. Contract countent. Buying and selling sweet potato leaves as feed for pigs can be considered legitimate because it has met the requirements in the pillars and in buying and selling. On the other hand buying and selling is also forbidden or too imperfect, is due to the utilization of sweet potato leaves are not in accordance with the teachings of Islam, namely to feed the cattle were forbidden for Muslims to consume. In Islamic law, those who saddudz dzari'ah.